Evthymios Papataxiarchis, Jean Cuisenier (éd.), 2005, «Grèce-Ελλάδα. Figures de Γ altérité», Ethnologie Française, XXXV, 2, Παρίσι, PU - Μάρκου Κατερίνα (The Greek Review of Social Research, 2016)
Δε διατίθεται περίληψη / no abstract available